Sidechain structure-activity relationships of cyclobutane-based small molecule αvβ3 antagonists - Throup, Adam; Zraikat, Manar Saleh; Gordon, Andrew; Jafarinejad Soumehsaraei, Shohreh; Haase, Kathrin D; Patterson, Laurence H; Cooper, Patricia A; Hanlon, Katherine; Loadman, Paul M; Sutherland, Mark; Shnyder, Steven D; Sheldrake, Helen M (MedChemComm, 2024)
The integrin family of cell surface extracellular matrix binding proteins are key to several physiological processes involved in tissue development, as well as cancer proliferation and dissemination. They are therefore attractive targets for drug discovery with cancer and non-cancer applications. We have developed a new integrin antagonist chemotype incorporating a functionalised cyclobutane ring as the central scaffold in an arginine-glycine-aspartic acid mimetic structure. Here, we report the synthesis of cyclobutanecarboxylic acids and cyclobutylamines with tetrahydronaphthyridine and aminopyridine arginine mimetic sidechains and masked carboxylic acid aspartic acid mimetic sidechains of varying length. Effective αvβ3 antagonists and new aspartic acid mimetics were identified in cell-based adhesion and invasion assays. A lead compound selected based on in vitro activity (IC 50 < 1 μM), stability ( t 1/2 > 80 minutes) and synthetic tractability was well-tolerated in vivo . These results show the promise of this synthetic approach for developing αvβ3 antagonists and provide a firm foundation to progress into advanced preclinical evaluation prior to progression towards the clinic. Additionally, they highlight the use of functionalised cyclobutanes as metabolically stable core structures and a straightforward and robust method for their synthesis. This important contribution to the medicinal chemists' toolbox paves the way for increased use of cyclobutanes in drug discovery. Cyclobutanes provide a versatile scaffold for the synthesis of small molecule integrin antagonists with good metabolic stability and in vivo tolerability.